APLIKASI BIMBINGAN SKRIPSI ONLINE PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS SAHID SURAKARTA - Syahru Romadhon Az Haru (Fakultas Sains, Teknologi dan Kesehatan Universitas Sahid Surakarta, 2019)
The process of thesis supervising at Sahid Surakarta University (USAHID) is meeting directly to the supervisor. However, students cannot meet supervisors every time since the supervisors are teaching, researching, community servicing or meetings. Thus, the process of thesis supervising is longer because of waiting for lecturers. Based on these problems, this final project will design and build an Online Thesis supervisions Application in the Informatics Engineering department at Sahid Surakarta University in order to facilitate students in conducting online thesis guidance. The method used observation, interviews and literature review. The application used PHP programming language and MySQL database. The application had been tested by blackbox and webqual testing. The results are applications of thesis supervision process without have not to meet with the lecturer. The supervision system covers uploading files to the clouds, and inputting the data for submission of thesis supervision with including the uploaded file link to the clouds. Thus, it can be accessed and edited by the supervisor. Students can print the results of thesis supervision on student user applications. The results of testing system using the black box method were all valid functions and the questionnaire on webqual testing with 4 parameters, namely quality of use, quality of information, quality of service interaction and quality of user satisfaction got an average score of 3,217. Therefore, the interval table can be interpreted that the user agrees to use this application.